Compositions and Interior Structures of the Large Moons of Uranus and Implications for Future Spacecraft Observations. Issue 1 (14th January 2023) - Castillo‐Rogez, Julie; Weiss, Benjamin; Beddingfield, Chloe; Biersteker, John; Cartwright, Richard; Goode, Allison; Melwani Daswani, Mohit; Neveu, Marc
Abstract: The five large moons of Uranus are important targets for future spacecraft missions. To motivate and inform the exploration of these moons, we model their internal evolution, present‐day physical structures, and geochemical and geophysical signatures that may be measured by spacecraft. We predict that if the moons preserved liquid until present, it is likely in the form of residual oceans less than 30 km thick in Ariel, Umbriel, and less than 50 km in Titania, and Oberon. The preservation of liquid strongly depends on material properties and, potentially, on dynamical circumstances that are presently unknown. Miranda is unlikely to host liquid at present unless it experienced tidal heating a few tens of million years ago. We find that since the thin residual layers may be hypersaline, their induced magnetic fields could be detectable by future spacecraft‐based magnetometers. However, if the ocean is maintained primarily by ammonia, and thus well below the water freezing point, then its electrical conductivity may be too small to be detectable by spacecraft. Lastly, our calculated tidal Love number ( k 2 ) and dissipation factor ( Q ) are consistent with the Q / k 2 values previously inferred from dynamical evolution models. In particular, we find that the low Q/k 2 estimated for Titania supports the hypothesis that Titania currently holds an ocean. Plain Language Summary: The major moons of Uranus, Miranda, Ariel, Umbriel, Titania, and Oberon, are interesting targets for a future space mission because they might host liquid at present. Studying these bodies would help address the extent of habitable environments in the outer solar system. We model their thermal, physical, and chemical evolution. Because their heat budget is limited, with little or no tidal heating at present, we find that most of the moons can preserve only a few tens of kilometers of liquid until present. Furthermore, if the oceans are maintained by antifreeze, such as ammonia and chlorides, then their electrical conductivities may be close to zero. In this case, the detection of a magnetic field induced in these oceans would be challenging. We explore additional geophysical, as well as compositional, observations that would reveal the existence of a deep ocean in these moons. None of the scenarios studied produce residual liquid in Miranda at present. Our simulations are consistent with constraints on the dissipative properties of the moons inferred from dynamical evolution models. Key Points: Most of the major Uranian moons may host a residual ocean a few tens of kilometers thick at present, except for Miranda Thermal metamorphism could create a late, second generation ocean in Titania and Oberon These models represent a baseline for the formulation of observations with the Uranus Orbiter and Probe